Interactive Storytelling - Chai, Edwin Yi Yun (2010)
The purpose of this interactive storytelling project is to create a storytelling application that breaks the linearity of traditional storytelling. The application will allow users to create interactive stories that require dynamic input and interaction from player-users during the creation as well as the storytelling process. Interactive storytelling has been on the rising in the past few years, particularly with the acceptance of Player Generated Content into the mainstream entertainment market. But, none of the software currently available is able to capture the true essence of interactive storytelling that this project aims to achieve.